Teaching Methods In Nahj Al-Balagha For Al-Shareef Al Radhi (D.406 AH) - Asst. Prof. Abdul- Hussain Ahmed Rasheed Al-Khafaji (PhD), (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Nahju al-Balagha is rich in various teaching methods introduced by Imam Ali Ibn Abi Talib (PBUH), which are based on the Holy Qur'an and the Prophet Mohammed (PBUH). These methods have a great impact on the methods of teaching and learning that emerged recently. The research aims at pointing out these teaching methods and making use of them in the educational process at the various stages of study to achieve the aim of the research, the researcher adopted many procedures including: determining the research methodology , population, sample, and the instrument. One of the findings of the research is that Nahj al-Balagha includes many methods of teaching. The researcher recommended that teachers read Nahj al-Balagha and employ it in teaching. The researcher suggests conducting a similar study that deals with the teaching methods in the collections attributed to ahl albeit (PBUT).